Maternal inhaled fluticasone propionate intake during pregnancy is detected in neonatal cord blood. (July 2016) - Battista, Marie-Claude; Boutin, Michel; Venne, Philippe; Blais, Lucie; Bérard, Anick; Lacroix, Marilyn; Patenaude, Julie; Guillemette, Laetitia; Cossette, Benoit; Hivert, Marie-France; Auray-Blais, Christiane
Background: Despite recommendations to use inhaled corticosteroids as treatment to control asthma during pregnancy, it is unknown whether inhaled fluticasone propionate (FP) reaches the fetus.Results & methodology: We collected maternal blood on the morning following delivery. FP was detected by ultra-performance LC–MS/MS (UPLC–MS/MS) in 9/17 asthmatic women using FP. Delay between last FP inhalation and maternal blood sampling ranged between 3 and 33 h and FP was detected in a range of 1.572–46.440 pg/ml. Among the nine offspring of these FP users, FP was detected in five cord blood samples. Delay between last predelivery FP inhalation and cord blood sampling ranged from 4 to 20 h and FP was detected in a range of 0.423–4.510 pg/ml.Conclusion: Our findings demonstrate placental passage of inhaled FP.